Antioxidant and antidiabetic activity of phenolic compounds extracted from Orthosiphon stamineus extracts - Abdul Mubdi, Nurazrin Ezrina (2019)
Orthosiphon stamineus Benth (Lamiaceae), locally called Misai Kucing, is a local herb that grows widely in Malaysia. It is gaining popularity and well-known plant in herbal medicine. The objective of this study is to identified and quantified the antioxidant activity and phenolic compounds using HPLC, HPLC-PDA-MS2 and HPLC with post-column on-line antioxidant detection based on 2,2'-azinobis-(3-ethylbenzothiazoline-6-sulfonic acid (ABTS) radical scavenging assay. The results had shown the phytochemicals in water extracts contained salvinalic acid, chlorogenic acid, caffeic acid and rosmarinic acid. Salvinalic acid and caffeic acid in O. stamineus extracts possess high Trolox Equivalent Antioxidant Ratio (TEAR) values by 0.74 and 0.50 respectively. O. stamineus has been scientifically proven to have hypoglycaemic and antihyperglycaemic activity. In this study, hypoglycaemic and antihyperglycaemic activity of O. stamineus water extracts in normal and diabetic rats (streptozotocin induced) was evaluated. In evaluation of hypoglycaemic activity of O. stamineus extracts in normal rats, medium doses (15 mg/kg) and high doses (30 mg/kg) significantly reduced blood glucose level to 4.5 mmol/L and 4.14 mmol/L after 6 (p ˂ 0.05) hours extracts administration. Metformin, 500 mg/kg also shows hypoglycaemic activity after 6 hours administration. The evaluation of antihyperglycaemic activity, the results showed that O. stamineus extracts significantly reduced fasting and postprandial hyperglycaemic particularly after 2 and 4 hours extracts administration at high doses (30 mg/kg). In conclusion, the usage of analytical instruments such as HPLC, HPLC-PDA-MS2 and antioxidant assays has prompted to identification of phenolic compounds and antioxidant activities in Malaysian traditional herbs. This study showed that O. stamineus water extract can be employed and suitable as dietary subordinate to deal with hyperglycemia in diabetes patients.